Are African Stock Markets Efficient? A Comparative Analysis Between Six African Markets, the UK, Japan and the USA in the Period of the Pandemic - Dias, Rui; M. Pereira, João; Cagica Carvalho, Luísa (Naše gospodarstvo/Our economy, 2022)
The aim of this study is to test and compare the efficient market hypothesis, in its weak form, on the stock markets of Botswana, Egypt, Kenya, Morocco, Nigeria, South Africa, Japan, the UK and the USA from 2 September 2019 to 2 September 2020. This study is based on the following research question: has the global pandemic (COVID-19) reduced the efficiency – in its weak form – of African financial markets compared to the mature markets of the UK, Japan and the USA? The results sustain the evidence that the random walk hypothesis is not supported by the financial markets analysed in the period of the global pandemic. The variance ratio values are lower than the unit, which implies that the returns are self-correlated over time. A reversion to the average is also observed, with no differences identified between mature and emerging financial markets. In corroboration, the Detrended Fluctuation Analysis (DFA) exponents show that the financial markets present signs of (in)efficiency in its weak form, thus showing persistence in the yields. This therefore implies the existence of long memories validating the results of the variance using the Wright’s Rank and Signs Test (2000), which prove the rejection of the random walk hypothesis.